2000
DOI: 10.1103/physrevlett.85.4960
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Driven Jahn-Teller Distortion in a Pyrochlore System

Abstract: The ground-state properties of the spin-1 antiferromagnetic Heisenberg model on the cornersharing tetrahedra, pyrochlore lattice, is investigated. By breaking up each spin into a pair of 1/2-spins, the problem is reduced to the equivalent one of the spin-1/2 tetrahedral network in analogy with the valence bond solid state in one dimension. The twofold degeneracy of the spin-singlets of a tetrahedron is lifted by a Jahn-Teller mechanism, leading to a cubic to tetragonal structural transition. It is proposed tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
233
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(242 citation statements)
references
References 18 publications
(26 reference statements)
7
233
1
1
Order By: Relevance
“…Previous studies have shown that spin-lattice coupling can lift the ground state degeneracy in frustrated magnets [11][12][13][14][15][16][17] . However, the detailed microscopic mechanism, i.e.…”
Section: (C) Shows That At 32 K (T < T N ) For H < 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that spin-lattice coupling can lift the ground state degeneracy in frustrated magnets [11][12][13][14][15][16][17] . However, the detailed microscopic mechanism, i.e.…”
Section: (C) Shows That At 32 K (T < T N ) For H < 10mentioning
confidence: 99%
“…Several different mechanisms to reduce frustration in the absence of an external magnetic field have been studied 11,[13][14][15][16][17][18][19][20][21][22] with Fddd symmetry at 6 K. 13 Elastic magnetic neutron scattering data obtained with 4 zero field (blue circles in Fig. 1 (a)) shows that in the low temperature phase the spins order long range with two characteristic magnetic wave vectors Q M = (1/2,0,1) and (1,0,0).…”
mentioning
confidence: 99%
“…7 While extensive studies on frustrated magnets have revealed that the triangular HAF may exhibit the magnetic LRO, 8,9,10,11,12,13,14,15,16,17,18 the Anderson's idea is still attracting much interest, and has been tested for its possible realization in other geometrically frustrated systems such as pyrochlore and Kagome HAF, and multiple ring exchange spin models. 19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35 Recently, Shimizu et al reported that in an organic Mott insulator with spin s = 1/2 on a triangular lattice, κ-(ET) 2 Cu 2 (CN) 3 , no magnetic LRO is observed down to 32 mK. 36 Their experimental results suggest the possibility of a new kind of a ground state including the spin liquid.…”
mentioning
confidence: 99%
“…Known systems with strong frustration have f ≈ 5-10, thereby opening a window of spin-liquid physics for T c < T < CW [4]. This degeneracy is fragile and usually small perturbations lift it: dipolar interactions plus disorder [5], spin-lattice coupling [6], and Dzyaloshinskii-Moriya interaction [7] are known mechanisms. In quantum models, quantum fluctuations can lift the degeneracy at temperature T = 0 [8][9][10].…”
mentioning
confidence: 99%